PENGARUH OKETANI MASSAGE TERHADAP KECUKUPAN ASI PADA IBU POST PARTUM DI PRAKTIK BIDAN MANDIRI (PBM) KASIH IBU KABUPATEN DELI SERDANG - Anuhgera, Diah Evawanna (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
Breastfeeding to babies is important in supporting the growth process. This is of course influenced by the production of breast milk so as to produce a good sufficiency of breast milk. Oketani massage can stimulate the oxytocin reflex release, and patient comfort This study used a quasi experimental study with a time series design. The sample in this study were normal post partum mothers on the first day in Primary Health Care Kasih Ibu as many as 16 respondents in the intervention group and 16 respondents in the control group. Data were collected through primary and secondary data. The research instruments were baby scales, observation sheets and standard procedures for massage oketani. Analysis of data used repeated measured Anova The results showed no significant difference between the two groups in terms of neonatal weight gain on day 1 before the intervention (P = 0.17). However, there was a statistically significant difference between the two groups after intervention at day 5 and 10 of the intervention (P <0.001). This study shows that Oketani massage compared to routine care increases the adequacy of breast milk through neonatal weight gain in nursing mothers. This study suggests that oketani massage in postpartum mothers can increase the adequacy of breast milk and this treatment can be used as an alternative nurse for normal post-partum mothers.